Clinical pharmacy education, practice and research : clinical pharmacy, drug information, pharmacovigilance, pharmacoeconomics and clinical research / Thomas, Dixon - Thomas, Dixon
Clinical Pharmacy Education, Practice and Research offers readers a solid foundation in clinical pharmacy and related sciences through contributions by 83 leading experts in the field from 25 countries. This book stresses educational approaches that empower pharmacists with patient care and research competencies. The learning objectives and writing style of the book focus on clarifying the concepts comprehensively for a pharmacist, from regular patient counseling to pharmacogenomics practice. It covers all interesting topics a pharmacist should know. This book serves as a basis to standardize and coordinate learning to practice, explaining basics and using self-learning strategies through online resources or other advanced texts. With an educational approach, it guides pharmacy students and pharmacists to learn quickly and apply. Clinical Pharmacy Education, Practice and Research provides an essential foundation for pharmacy students and pharmacists globally. Covers the core information needed for pharmacy practice coursesIncludes multiple case studies and practical situations with 70% focused on practical clinical pharmacology knowledge. Designed for educational settings, but also useful as a refresher for advanced students and researchers